The investigation on the factors that affect the resistance of drain-to-source in semiconductor packaging - Chua, King Lee (2004)
The objectives of the project is to investigate the characteristics contact resistance of the silicon lead-frame interface using ECA die attach materials, and to evaluate the factors contributing to the increase of interface resistively in semiconductor packaging. This project was done at ON Semiconductor where silver-filler epoxybased adhesive chips were investigated. Tektronix 370B Programmable Curve Tracer with picoprobing is used to measure RoN of the chips. Nondestructive techniques such as X-ray and SAM used to examine internal defect and cross sectional analysis was done using SEM. Few factors were found affect RoN. Those factors are capacitance due to trap charges during fabrication, supply voltage, thermal management of the package, delamination between die attachments, thickness of the epox)' and copper dioxide of the lead-frame.